Remote Client Administration (International Journal of Engineering and Computer Science, 2014)
Remote Client Administration is a service offering a full function network, which provides its authorized users with the ability to monitor and manage the connected clients. This software will benefit the administrator in lab/office to manage the clients. This project gives an administrative power to the server. The software mainly provides services chatting through text, audio and sharing resources between computers. The administrator system provides some restrictions for the clients. It gives the system a role of administrator in an organization. Our system is highly user friendly and interacting. Our system can view all users connected with the server. Administrator system can view the hardware status of the client and all process currently running under the client machine. Our system helps the administrator to kill the unwanted process running on the client machine. The administrator can shut down, restart and log off the client system. We are confident that this project will benefit every administrator in delivering his duties.